Quality of servicing of social services recipients that are in difficult life circumstances: the scientific approaches - Ільчук, Л. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article examines scientific approaches to the quality of service in the provision of social services, especially for those in difficult life situations. Quality is seen as the level of satisfaction of service users and is determined primarily by the value of these services. The attention is focused on the fact that the problem of quality has a universal character in the modern world, and its decisions directly affect the development and further functioning of the social sphere of Ukraine. It is noted that the services in general and social services, in particular, in comparison with the goods, have certain features that must be taken into account in the study, namely intangibility; inseparability; inconstancy; shortterm; lack of ownership.